2009
DOI: 10.1371/journal.pone.0007818
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association Analysis of the Functional c.714T>G Polymorphism and Mucosal Expression of Dectin-1 in Inflammatory Bowel Disease

Abstract: BackgroundDectin-1 is a pattern recognition receptor (PRR) expressed by myeloid cells that specifically recognizes β-1,3 glucan, a polysaccharide and major component of the fungal cell wall. Upon activation, dectin-1 signaling converges, similar to NOD2, on the adaptor molecule CARD9 which is associated with inflammatory bowel disease (IBD). An early stop codon polymorphism (c.714T>G) in DECTIN-1 results in a loss-of-function (p.Y238X) and impaired cytokine responses, including TNF-α, interleukin (IL)-1β and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
(29 reference statements)
2
27
0
1
Order By: Relevance
“…This suggests that colitis in Clec7a −/− mice is not aggravated by a typical fungal infection, but that other aspects of host–fungal interactions affecting the mycobiota might be involved. Consistent with the mouse models, patients carrying a two-marker CLEC7A haplotype developed more severe refractory ulcerative colitis supporting a possible role of dectin-1 in severity 16 , but not susceptibility to intestinal disease 87 . Furthermore, dectin-1 deficiency is also associated with increased colonization of Candida spp.…”
Section: Mucosal Immunity To Fungisupporting
confidence: 65%
“…This suggests that colitis in Clec7a −/− mice is not aggravated by a typical fungal infection, but that other aspects of host–fungal interactions affecting the mycobiota might be involved. Consistent with the mouse models, patients carrying a two-marker CLEC7A haplotype developed more severe refractory ulcerative colitis supporting a possible role of dectin-1 in severity 16 , but not susceptibility to intestinal disease 87 . Furthermore, dectin-1 deficiency is also associated with increased colonization of Candida spp.…”
Section: Mucosal Immunity To Fungisupporting
confidence: 65%
“…Actually, we showed that the proportion of L. salivarius was reduced in intestinal flora of IBD patients, suggesting a protective role of this commensal species. In this context, it was reported that Dectin-1 expression is upregulated in IBD patients (de Vries et al, 2009), and fecal calprotectin is one good marker of IBD (Foell et al, 2009). On the other hand, two single-nucleotide polymorphisms in CLEC7A are associated with medically refractory UC, in which fungal infection may play a pathogenic role (Iliev et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…albicans is a common commensal of the intestinal tract, and it was reported to increase the severity of intestinal inflammation in murine models of colitis (10,11). The b-glucan receptor dectin-1 is involved in this effect, and polymorphisms in this receptor have been associated with the severity of ulcerative colitis (11) but not with the susceptibility to ulcerative colitis or Crohn's disease (36). Little is known about the mechanisms through which C. albicans may influence autoinflammatory diseases, such as Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%